2009
DOI: 10.1007/s00011-009-0013-y
|View full text |Cite
|
Sign up to set email alerts
|

Local and systemic chemokine patterns in a human musculoskeletal trauma model

Abstract: There is fundamental difference between local and systemic chemokine kinetics in the human trauma model studied. High postoperative concentrations of CCL2 and CXCL8 at the site of inflammation form a gradient that contributes to the recruitment of neutrophils and monocytes at the trauma site.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 45 publications
1
2
0
Order By: Relevance
“…In agreement with previous studies, a marked increase in IL-6 and IL-10 was seen day 1 following surgery. Moreover, IP-10 levels decreased significantly the day after surgery, in agreement with a previous study of THA 15,18,45 . This could result from IL-10mediated inhibition of IP-10 as previously reported, or IP-10 peaking early to recruit T cells to damaged tissue followed by a marked decrease, as seen for T cells 16,46,47 .…”
Section: D6mwtsupporting
confidence: 92%
“…In agreement with previous studies, a marked increase in IL-6 and IL-10 was seen day 1 following surgery. Moreover, IP-10 levels decreased significantly the day after surgery, in agreement with a previous study of THA 15,18,45 . This could result from IL-10mediated inhibition of IP-10 as previously reported, or IP-10 peaking early to recruit T cells to damaged tissue followed by a marked decrease, as seen for T cells 16,46,47 .…”
Section: D6mwtsupporting
confidence: 92%
“…5). Bastian et al clearly showed a significant acute post-traumatic rise in monocyte and neutrophil levels as well as total WBC count amongst subjects who had total hip replacement arthroplasty [24]. This work confirmed that chemokine burst arising from tissue damage was responsible for the observed neutrophilia and monocytaemia.…”
Section: Physiologic and Clinical Implicationsmentioning
confidence: 56%
“…70 We observed several other patterns consistent with previous literature. These include MIF (upregulated 71 ), TRAIL (upregulated and previously reported to be increased in elderly osteoporotic fractures 72 ), and Eotaxin (downregulated, and previously reported to be downregulated in musculoskeletal surgical trauma 67,73 ).…”
Section: Data and Code Availabilitymentioning
confidence: 98%